Розроблення програмного маршрутизатора з автоматичним розгортанням віртуальних вузлів - Климаш, М. М.; Романчук, В. І.; Поліщук, А. В.; Панченко, О. М.; Бешлей, М. І.; Klymash, M. M.; Romanchuk, V. I.; V Polishuk, A.; Panchenko, O. M.; Beshley, M. I. (Видавництво Львівської політехніки, 2017)
Описано розгортання віртуальних маршрутизаторів відповідно до гнучкого розподілу віртуального часу доступу до процесора. Розроблено програмну модель марш- рутизатора з набором сучасних механізмів та алгоритмів обслуговування інформаційних потоків. На основі програмної моделі маршрутизатора розширено набір функціональних можливостей пристрою: додано режим розгортання віртуальних вузлів із можливістю гнучкого управління структурними параметрами. Досліджено якість обслуговування IPTV трафіку на основі розробленої моделі програмного маршрутизатора з можливістю розгортання віртуальних обслуговуючих пристроїв класового призначення.

The thesis is devoted to solving scientific and technical task of improving service quality indicators for streaming traffic in multiservice network with node resource virtualization. A model to maintain the required quality of service parameters for information traffic based on virtualization technology of network device and adaptive management of the structural parameters of the node is proposed. In this paper we propose to consider the option of network device virtualization by installing the router on one physical server core. Thus, to investigate the operation principle of virtual routers we control allocation of processor time to each process. For this we must determine which CPU processes used by the operating system Linux-Ubuntu 14.04. We developed the model of software router with a set of modern mechanisms and algorithms service information flows. Using the model of the router we enhanced functionality of the device: added mode of deployment of virtual nodes with the possibility of flexible management of the structural parameters. Usign the developed software router model, we conducted the research of service quality of IPTV traffic through deployment of virtual devices for processing traffic of different service classs. Based on the experiment in multiservice network, it was found out that the developed models for dynamic network device virtualization provide the ability to select the minimum amount of network resources to guarantee a given level of service quality and enables 25–30% increase in service quality of real-time streaming traffic with respect to delay and jitter.
Design of software router with automatic deployment at virtual nodes
Keywords: віртуальний маршрутизатор; програмний маршрутизатор; буфер; параметри якості обслуговування; віртуалізація; virtual router; program router; buffer; QoS parameters; virtualization; 004.9 621.39